2004
DOI: 10.1164/rccm.200402-215oc
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of 60% Oxygen and Neutrophil Influx on Alveologenesis in the Neonatal Rat

Abstract: The lungs of newborn rats exposed to 60% oxygen for 14 days develop an injury that shares morphologic similarities to human bronchopulmonary dysplasia (BPD). Neutrophil influx into the lung, as part of an inflammatory response, may play a pivotal role in the development of BPD. A neutrophil chemokine, cytokine-induced neutrophil chemoattractant-1, which signals through the neutrophil CXC chemokine receptor-2, is increased in the lung tissue of newborn rats exposed to 60% oxygen. The purpose of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
125
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 44 publications
12
125
3
2
Order By: Relevance
“…Control experiments confirmed that hyperoxia did not stimulate expression of the mT/mG reporter ( Figure E2) and that it did not activate excision of mT red in the absence of doxycycline. To confirm that the expansion of type II cells was not related to their morbidity, the study was repeated with 60% oxygen, which is still sufficient to disrupt lung development (20,33). Similar to the effects seen with 100% oxygen, EGFP was readily detected in alveolar cells of mice exposed to 60% oxygen ( Figures 5B and 5C).…”
Section: Neonatal Hyperoxia Stimulates Expansion Of Type II Cellsmentioning
confidence: 72%
“…Control experiments confirmed that hyperoxia did not stimulate expression of the mT/mG reporter ( Figure E2) and that it did not activate excision of mT red in the absence of doxycycline. To confirm that the expansion of type II cells was not related to their morbidity, the study was repeated with 60% oxygen, which is still sufficient to disrupt lung development (20,33). Similar to the effects seen with 100% oxygen, EGFP was readily detected in alveolar cells of mice exposed to 60% oxygen ( Figures 5B and 5C).…”
Section: Neonatal Hyperoxia Stimulates Expansion Of Type II Cellsmentioning
confidence: 72%
“…First, increased expression of CXCR2 was observed in hyperoxic lungs [120]. Following exposure to 80% O 2 for 6 days, CXCR2 −/− mice showed reduced neutrophil sequestration, which is associated with significantly decreased lung vascular permeability, edema and injury [121].…”
Section: Proinflammatory Responses In Hyperoxic Lung Injurymentioning
confidence: 98%
“…This strategy suppressed pulmonary inflammation and enhanced lung growth. 23 Pro-and anti-inflammatory cytokines Besides IL-8, other proinflammatory cytokines such as TNF-a, IL-1 and interleukin-6 (IL-6) are important mediators in the early inflammatory response. These cytokines are synthesized by alveolar macrophages, fibroblasts, type II pneumocytes and endothelial cells upon stimulation by hypoxia, hyperoxia, endotoxin, other bacterial cell wall constituents, and biophysical factors.…”
Section: Inflammatory Cells Endothelial Interactions and Chemotaxismentioning
confidence: 99%